Answer: Um, the answer is U= –144.
Step-by-step explanation:
Answer:
156
Step-by-step explanation:
221/17=13
13*12=156
Answer:
$156
Step-by-step explanation:
221/17=x/12
221*12=17x
2652=17x
156=x
Answer:
Step-by-step explanation:
Length of fence = Perimeter of triangle
= 10 + 20 + 15
Length of the fence = 45 m
Cost of fencing per meter = Rs. 25
Cost of fencing 45 m = 25 * 45
= Rs. 1125
Lengths of the three sides of triangle are 10m,20m and 15m.
Perimeter of the ∆
Answer choices are below
A. 2 units
B. 2.75 units
C. 5.5 units
D. 11 units
The original circle's radius cannot be definitively determined from the question as is, because the dilated circle's radius is not specified. However, if the dilated circle's radius is known, the original radius can be found by dividing the dilated radius by the scale factor, which is 2 in this case.
The question represents a geometric concept in Mathematics, specifically dealing with dilation of a circle. In dilation, a figure is altered in size without changing its shape. If a circle is dilated by a scale factor of 2, meaning it has been made twice as large, the radius of the dilated circle will be two times the radius of the original circle. If the scale factor is 2, the radius's length will be halved to get the measurement of the original circle's radius. Therefore, without the specific measurement of the dilated circle's radius, we can't definitively give the original circle's radius from the options given (A. 2 units, B. 2.75 units, C. 5.5 units, D. 11 units).
#SPJ3
why does y=mx+b ?
Answer:
The coordinates of every point on the line will solve the equation if you substitute them in the equation for x and y. The equation of any straight line, called a linear equation, can be written as: y = mx + b, where m is the slope of the line and b is the y-intercept
Step-by-step explanation:
lol thx for the points
-3 -2 -N
-1
-2
The equation of this line is
y = -x - 1. Which of the
following shows a way that
we could change the
equation to make the
line steeper?
N
A. y = -x + 5
B. y = -4x - 1
C. y = -x - 3